Pengaruh Audit Internal dan Akuntabilitas Sektor Publik terhadap Kualitas Penyajian Laporan Keuangan dalam Mengelola Alokasi Dana Desa di Kecamatan Pontang Tahun 2022 - Pamungkas, Giantoro; Puri, Pustika Ayuning; Yanto, Deri (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The purpose of this study was to find out the effect of internal audit and public sector accountability on the quality of presentation of financial reports in managing village fund allocations in Pontang District in 2022. This study used a quantitative approach with data collection techniques using a questionnaire. The population in this study were 30 village officials in the Pontang District, while the sample used the saturated sampling technique, which is a sampling technique when all members of the population are used as samples, so that the samples taken in this study were 30 people. The results of this study in hypothesis 1 there is an effect of internal audit on the quality of presentation of financial reports in managing village fund allocations in Pontang District in 2022. Hypothesis 2 there is an effect of public sector accountability on the quality of presentation of financial statements in managing village fund allocations in Pontang District in 2022. Hypothesis 3 there is the influence of internal audit and public sector accountability together on the quality of presentation of financial reports in managing village fund allocations in Pontang District in 2022.